The Influence of Leadership Style and Organizational Culture on Job Satisfaction of the CUG Konsepsi Filosofi Petani Pancur Kasih Pontianak - Arestia, Nova (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
The purpose of this study is to determine the influence of leadership study variables and organizational culture both simultaneously and partially on the job satisfaction of Credit Union Gerakan Konsepsi Filosofi Petani Pancur Kasih Pontianak Activists. The analytical method used is referred to as the associative method and multiple linear regression analysis. The respondents of this study are all Credit Union Gerakan Konsepsi Filosofi Petani Pancur Kasih Pontianak Activists totalling 33 people. The results of applying this study to an F test show that there is a simultaneous influence between leadership style variables and organizational culture variables on job satisfaction while the results of hypothesis testing using a T-test show that there is a partial influence between leadership style variables on job satisfaction, but there is no partial influence between organizational culture variables on job satisfaction. The conclusion from the results of this study is that the leadership style variables and organizational culture variables have a simultaneous influence on job satisfaction, and there is a partial influence of leadership style variables on job satisfaction but there is no influence of organizational culture variables on job satisfaction.